MENINGKATKAN KEMAMPUAN KONSEP BILANGAN MELALUI METODE MONTESSORI PADA ANAK KELOMPOK A DI RA NURUL HIKMAH PALANGAN JANGKAR - Suyanti Suyanti; Hozeiningsih Hozeiningsih (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2021)
The development of the concept of children's numbers is one of the important things in the growth of early childhood. The concept of number is an abstract form that provides information on the number of objects symbolizing numbers which can be numbers or writing that can be stimulated in early childhood. The learning process of introducing the concept of numbers to make it fun for children uses learning media to group objects through number cards and picture cards. The formulation of the problem in this study is (1) How to improve the ability of number concepts through the Montessori method in group A children at RA Nurul Hikmah Palangan Angkar Situbondo (2) How the results of increasing number concept skills through the Montessori Method in group A children at RA Nurul Hikmah Palangan Angkar Situbondo. This research refers to Classroom Action Research (CAR) which is carried out by planning, implementing, observing and reflecting on actions through cycles. The results of this study are (1) The process of implementing the Montessori Method one by one from students grouping objects in a sequence of 1-10 using number cards and picture cards, after finishing counting, children will begin to distinguish shapes, colors and sizes of objects. (2) The results showed an increase in the ability to recognize the concept of numbers through the Montessori Method, namely the pre-cycle percentage value of 20%, after the implementation of the first cycle it reached 53%, the second cycle the indicator achievement increased by the percentage of 86.6%. In each cycle there has been an increase in the development of number concept skills in children in recognizing numbers.